1996
DOI: 10.1046/j.1365-2133.1996.d01-1068.x
|View full text |Cite
|
Sign up to set email alerts
|

Coexpression of p21Waf1/Cip1 and p53 in sun-exposed normal epidermis, but not in neoplastic epidermis

Abstract: Wild-type p53 accumulation induced by DNA damaging agents such as ultraviolet (UV) radiation, gamma-irradiation and drugs, may arrest the cell cycle until DNA damage is repaired. p21Waf1/Cip1 is a cyclin-dependent kinase (CDK) inhibitor induced by wild-type p53. CDK is activated by cyclin and progresses the cell cycle. On the other hand, CDK inhibitors inhibit CDK activity to arrest the cell cycle. Thus, p21Waf1/Cip1 is thought to mediate the signal of p53 induced by DNA damaging agents to arrest the cell cycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
7
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 11 publications
2
7
0
Order By: Relevance
“…Coexpression of p53 and p21 was seen in only 2 cases in our material. This con®rms reports from other studies (28,29) and probably indicates the defective action of a mutated p53 and p21 induction by a p53-independent pathway. Colocalization is the rule when the physiological p53/p21 response to UV radiation is studied (26,43).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Coexpression of p53 and p21 was seen in only 2 cases in our material. This con®rms reports from other studies (28,29) and probably indicates the defective action of a mutated p53 and p21 induction by a p53-independent pathway. Colocalization is the rule when the physiological p53/p21 response to UV radiation is studied (26,43).…”
Section: Discussionsupporting
confidence: 91%
“…The existence of upstream inducers of p21 other than p53 is reported in a number of papers (26,32,33). Expression of p21 in SCC is usually independent of p53 (28,29), even in non-skin SCCs (34,35).…”
mentioning
confidence: 98%
“…13 is supported by the rapid (Ͼ50% within 2 h) decrease in the proportion of keratinocytes engaged in DNA synthesis after irradiation with UVB (unpublished data). It is thought that the major mediator of cell cycle arrest in UVirradiated cells is the p53 tumor suppressor (29). Surprisingly, we found that UVB irradiation of HEKn (p53-proficient cells [ Fig.…”
mentioning
confidence: 39%
“…In epidermis, p21 Cip1 levels increase in response to cell stress, and it is heterogeneously expressed in skin cancer cells (14,(21)(22)(23)(24). Of particular interest is the fact that p21…”
Section: Sulforaphane (Sfn)mentioning
confidence: 99%